Evaluating the level of diffusion of social networking sites among Malaysian university students - Embi, Mohamed Amin; Gabarre, Serge; Gabarre, Cecile; Hamat, Afendi; Din, Rosseni (Canadian Center of Science and Education, 2014)
Although Malaysians have been reported to be the heaviest social networking users, no survey had been conducted in the country to evaluate the level of diffusion of these sites. A nation-wide survey was conducted during two months to evaluate the membership, usage pattern, and perceptions of social networking sites among 6498 Malaysian university students. This article provides descriptive statistics and interprets the results in light of current literature and similar surveys conducted in other countries. Results revealed that a large majority of students were members of Facebook which they used on a daily basis mostly, but not exclusively to connect with their friends. The article concludes with opportunities to include such sites in formal and informal learning.